Immune approaches beyond traditional immune checkpoint inhibitors for advanced renal cell carcinoma - Albert Jang; Jake N. Lichterman; Jeffrey Y. Zhong; Jonathan E. Shoag; Jorge A. Garcia; Tian Zhang; Pedro C. Barata (Taylor & Francis Group, 2023)
ABSTRACTRenal cell carcinoma (RCC), especially clear cell RCC, is generally considered an immunotherapy-responsive cancer. Recently, the prognosis for patients with locally advanced and metastatic RCC has significantly improved with the regulatory approvals of anti-PD-1/PD-L1/CTLA-4 immune checkpoint inhibitor (ICI)-based regimens. Yet in most cases, RCC will remain initially unresponsive to treatment or will develop resistance over time. Hence, there remains an unmet need to understand what leads to ICI resistance and to develop novel immune and nonimmune treatments to enhance the response to ICIs. In this review, we highlight recently published studies and the latest clinical studies investigating the next generation of immune approaches to locally advanced and metastatic RCC beyond traditional ICIs. These trials include cytokines, gut microbiota-based therapies, novel immune checkpoint agents, vaccines, and chimeric antigen receptor T cells. These agents are being evaluated as monotherapy or in combination with traditional ICIs and will hopefully provide improved outcomes to patients with RCC soon.